Important factors to remember when constructing a cross-site scripting prevention mechanism - Md. Maruf Hassan; Badlishah R. Ahmad; Ashrafia Esha; Rafika Risha; Mohammad S. Hasan (Bulletin of Electrical Engineering and Informatics, 2022)
Web application has become an essential part of daily activities to provide easy accessibility that ensures better performance. It is a platform where sensitive information such as username, password, credit card details, operating system and software version. is stored that attracts intruders to generate most of their attacks. Intruders can steal valuable data by compromising web application security flaws; cross site scripting (XSS) vulnerability is one of these. Several studies have been conducted in order to prevent the XSS vulnerability. In this research, we searched Scopus Indexed articles published in the last 11 years (between 2008 and 2020) using two keywords (“XSS attack prevention” and “XSS prevention”). The purpose of this study was to conduct a literature review on XSS prevention techniques e.g., strengths and weaknesses, including structural issues and real-time deployment location in order to extract valuable information. This review identified 14 articles among the 25 selected articles that provided various suitable prevention techniques for XSS attacks. Seven articles are based on tools that have been implemented and take into account design, coding, testing, and integrating validation processes, six articles are about server site solutions, and one is about automatic mitigation solutions. As a result, this research will be invaluable in guiding the advancement of XSS prevention techniques.